Placental Transfer of IgG Antibodies Specific to Klebsiella and Pseudomonas LPS and to Group B Streptococcus in Twin Pregnancies. (February 2015) - Stach, S. C. L.; Brizot, M. L.; Liao, A. W.; Palmeira, P.; Francisco, R. P. V.; Carneiro‐Sampaio, M. M. S.; Zugaib, M.
Abstract Group B Streptococcus (GBS), Klebsiella spp. and Pseudomonas spp. are important aetiological agents of neonatal infections in Brazil. There is a lack of data in the literature regarding the specific transport of immunoglobulin G (IgG) against these pathogens in multiple pregnancies. Maternal (n = 55) and umbilical cord (n = 110) blood samples were prospectively collected at birth from 55 twin pregnancies. The factors associated with cord levels and transfer ratios of IgG against GBS, Klebsiella and Pseudomonas were examined. The IgG umbilical cord serum levels specific to GBS, Klebsiella LPS and Pseudomonas LPS were significantly associated with maternal‐specific IgG concentrations and the presence of diabetes. The anti‐Klebsiella IgG cord serum concentrations were also related to birthweight and the presence of hypertension. The transfer ratios against GBS and Pseudomonas LPS were associated with maternal‐specific IgG concentrations. The transfer ratios for GBS and Pseudomonas LPS were associated with gestational age at delivery and the presence of diabetes, respectively. None of the examined parameters were related to Klebsiella LPS transfer ratios. We conclude that in twin pregnancies, specific maternal IgG serum concentrations and diabetes were the parameters associated with umbilical cord serum IgG concentrations reactive with the three pathogens investigated. All the other parameters investigated showed different associations with neonatal‐specific IgG levels according to the antigen studied. There was no uniformity of the investigated parameters regarding association with placental IgG transfer ratios against the GBS, Pseudomonas LPS and Klebsiella LPS.